RONC-25. A CASE OF PEDIATRIC PONTINE GLIOMA TREATED WITH GAMMA KNIFE SURGERY. (4th December 2020) - Kaneko, Satoshi; Kiyokawa, Juri; Hirota, Shin; Murota, Yasuhiro; Ishikawa, Mariko; Yamaoka, Hiroto; Yoshimura, Masataka; Yamamoto, Masaaki; Yamamoto, Shinji
Abstract: BACKGROUND: Pediatric brainstem gliomas rarely occur and are a heterogeneous group of diseases, which increases the difficulty of treatment strategy. Here, we present a case of pediatric pontine glioma treated with Gamma Knife surgery (GKS) after open biopsy. CASE DESCRIPTION: An 11-year-old boy presented with diplopia due to the left MLF syndrome. MRI showed a well-circumscribed, protruding tumor with partial gadolinium enhancement in the dorsal pons. An open biopsy was performed via the suprafacial triangle following midline suboccipital approach. Histological examinations revealed high cellularity and mild atypia. Immunohistochemistry demonstrated positive stain for GFAP and Olig2 antibodies, and negative for p53 protein. The Ki67-labeling index was 6.8%. Pyrosequence analysis indicated IDH1/2 wild type (wt), BRAF V600 wt, H3F3A K27 wt, FGFR1 wt, and TERT wt. The final diagnosis was pediatric diffuse astrocytoma, WHO grade II, pons. GKS was performed one month after the biopsy. After transient worsening of the symptom, it disappeared gradually. The tumor is stable for three years with mild shrinkage of the size. DISCUSSION: Gross total resection (GTR) of pediatric low-grade, brainstem gliomas may result in a good prognosis. However, unlike pilocytic astrocytoma, diffuse astrocytoma is not easy to perform GTR without any complications. There are some reports regarding GKS for brainstem gliomas, which prove an increase in progression free survival rate. No marked tumor regression is achieved in our case, but tumor growth is well-controlled so far. CONCLUSION: GKS after biopsy can be a useful treatment option for pediatric low-grade brainstem gliomas.